Ukraine’s place among European countries by the level of human capital: a socio-geographical dimension - Kryvolapov, Valeriy (Human Geography Journal, 2026)
The article explores regional disparities in human capital development among European countries through the lens of socio-geographical analysis. Particular attention is given to the methodological challenges of measuring human capital using existing international indices such as HCI, HCI+, HDI, SPI, and GHCI. The study demonstrates that conventional composite indicators provide only generalized rankings and do not fully capture the internal structure and territorial differences of human capital across Europe.To address these limitations, the paper develops a methodological approach based on a multidimensional system of indicators reflecting the key components of health and education. The analysis includes life expectancy, healthcare infrastructure quality, average years of schooling, learning-adjusted years of schooling, and government expenditure on tertiary education per student. Using statistical data for 36 European countries, the indicators were standardized and examined through hierarchical cluster analysis employing Ward’s algorithm.The findings reveal six distinct clusters of European countries that differ significantly in the balance between educational and health-related dimensions of human capital. Countries of Northern and Western Europe demonstrate the highest overall levels of human capital due to advanced healthcare systems, high-quality education, and substantial investment in higher education. Meanwhile, lower positions are occupied mainly by post-socialist countries, especially those remaining outside the European Union.The paper also investigates Ukraine’s comparative position within the European context. Ukraine was classified into the cluster with the lowest aggregate indicators of human capital. However, despite weak healthcare-related indicators and insufficient educational financing, the country maintains comparatively strong educational performance in terms of schooling duration and quality-adjusted learning outcomes.The study highlights the analytical potential of cluster analysis for identifying territorial patterns and typological differences in human capital development. The proposed approach contributes to socio-geographical research methodology and may serve as a basis for further comparative studies of regional human capital disparities and public policy assessment in Europe.